High-strength alloy material based on rail transit vehicle and processing technology of high-strength alloy material
By using modified graphene oxide and hyperbranched epoxy compounds in rail transit vehicle applications, the problem of poor corrosion, fire resistance and forming performance of magnesium alloys in rail transit vehicles is solved, and high-strength alloys are realized Excellent performance of the material.
Patent Information
- Application Number
- CN202510047218.0
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2025-01-13
- Publication Date
- 2025-02-21
- Estimated Expiration
- 2045-01-13
AI Technical Summary
Magnesium alloys face problems such as corrosion, fire resistance, poor forming performance and welding defects in rail transit vehicles, which limit their application in large components.
A high-strength alloy material and its processing technology include smelting and casting of ingots at 740-760°C, followed by solid solution and aging treatment, followed by the preparation of corrosion-resistant coatings using modified graphene oxide and hyperbranched epoxy compounds. , coated on the surface of the alloy material to form a corrosion-resistant coating.
It significantly improves the corrosion resistance, fire resistance and mechanical properties of the alloy material, enhances the adhesion between the coating and the substrate, extends the service life, and shows better anti-corrosion effect in humid environments.
Smart Images

Figure SMS_1
Abstract
Description
Technical Field
[0001] The present invention relates to the technical field of alloy materials, and in particular to a high-strength alloy material for rail transit vehicles and a processing technology thereof. Background Art
[0002] With the increasing demand for weight reduction of high-speed train bodies and key components, traditional materials such as aluminum alloys and stainless steel have been gradually replaced by new light metal materials. As an important light metal material, magnesium alloy has a density of only 2 / 3 of aluminum alloy, but its mechanical properties are comparable to those of aluminum alloy, showing great application potential.
[0003] However, magnesium alloys face many challenges in application technology. Due to their low potential and active chemical properties, magnesium alloys are prone to corrosion, resulting in a rapid degradation rate, especially in humid or salt spray environments, which affects their service life and limits their promotion and application. Therefore, effective surface treatment is required. In addition, magnesium alloys have a low ignition point, which significantly increases the difficulty of fire safety design for rail transit vehicles; high-strength magnesium alloys have poor plasticity during forming processing, especially under high temperature conditions, and their forming performance will be limited, resulting in low production efficiency.
[0004] Magnesium alloys have poor thermal conductivity, large thermal expansion coefficient, and are easily oxidized. During the welding process, they are prone to defects such as coarse grains, large thermal stresses, and oxidation inclusions. At the same time, their process adaptability to welding with dissimilar metals is poor, which limits their application in large components.
[0005] Therefore, we propose a high-strength alloy material and its processing technology based on rail transit vehicles. Summary of the invention
[0006] The object of the present invention is to provide a high-strength alloy material based on rail transit vehicles and a processing technology thereof to solve the problems raised in the prior art.
[0007] To achieve the above object, the present invention provides the following technical solutions: A processing technology for high-strength alloy materials for rail transit vehicles comprises the following steps: Step S1: smelting the raw material at 740-760°C, cooling it to 720-730°C after melting, keeping it warm for 10-20 minutes, and casting it to obtain an ingot; Step S2: subjecting the ingot to solution treatment and aging treatment in sequence to obtain an alloy material; Step S3: Evenly mix the composite, mica powder, curing agent and epoxy diluent, add epoxy resin, defoaming agent and leveling agent, and perform ultrasonic treatment to obtain a corrosion-resistant coating; grind, polish, clean and dry the surface of the alloy material in sequence, apply the corrosion-resistant coating, and after curing, form a corrosion-resistant coating to obtain a high-strength alloy material.
[0008] Furthermore, the raw material includes the following chemical components in mass percentage: Zn: 1-2%, Y: 3.6-4.2%, Gd: 1.2-1.4%, Zr: 0.4-0.6%, Ca: 0.05-0.10%, Sn: 0.3-0.5%, and the balance is Mg.
[0009] Furthermore, the solution treatment process is to keep the temperature at 515-535°C for 8-12 hours and then quench with water.
[0010] Furthermore, the aging treatment process is to keep the temperature at 220-260° C. for 10-14 hours and air cool.
[0011] Furthermore, the corrosion-resistant coating comprises the following components by weight: 50-60 parts of epoxy resin, 5-15 parts of compound, 10-20 parts of mica powder, 10-20 parts of epoxy diluent, 8-12 parts of curing agent, 0.2-0.3 parts of defoaming agent, and 0.1-0.2 parts of leveling agent.
[0012] Furthermore, the epoxy resin is E51 epoxy resin.
[0013] Furthermore, the preparation method of the composite is as follows: Step (1): uniformly mix polyethyleneimine and phosphate buffer, adjust the pH value of the system to 5.0-5.5 with nitric acid, add caffeic acid and 1-(3-dimethylaminopropyl)-3-ethylcarbodiimide, react for 2-3 hours to obtain a modified polyethyleneimine solution, dropwise add a mixed solution of graphene oxide and DMF, drip for 30-50 minutes, react for 6-8 hours, cool to room temperature, filter, wash and dry to obtain modified graphene oxide; Step (2): under nitrogen protection, salicylaldehyde and anhydrous ethanol are mixed evenly, ethylenediamine is added dropwise for 30-50 minutes, the mixture is reacted at 70-80°C for 3-5 hours, the mixture is cooled to room temperature, filtered, washed and dried to obtain a hydroxyl-containing monomer; under nitrogen protection, the hydroxyl-containing monomer, castor oil triglycidyl ether and tetrabutylammonium bromide are mixed evenly, the mixture is reacted at 70-80°C for 4-6 hours, the mixture is cooled to room temperature, filtered, washed and dried to obtain a hyperbranched epoxy compound; Step (3): ultrasonically disperse the modified graphene oxide in deionized water, adjust the pH to 9-10 with sodium hydroxide, add the hyperbranched epoxy compound and mix evenly, react for 6-8 hours, then add octadecyl mercaptan, perfluorodecyl mercaptan and 2-hydroxy-2-methylpropiophenone and mix evenly, irradiate with ultraviolet light, wash, filter and dry to obtain a composite.
[0014] In the above technical scheme, the amino group in polyethyleneimine reacts with the carboxyl group in caffeic acid to introduce a catechol group with adhesion properties, and then the polyethyleneimine containing a large number of amino groups is used as a bridge to react with the epoxy group in graphene oxide to introduce the amino group into the graphene oxide to obtain modified graphene oxide; then the amino group on the modified graphene oxide reacts with a hyperbranched epoxy compound, and finally octadecyl mercaptan and perfluorodecanethiol are added, and a hydrophobic long-chain alkyl group and a fluorine-containing group are introduced through a thiol-ene click reaction to obtain a composite with anti-corrosion and hydrophobic properties.
[0015] Furthermore, in the step (1), the mass ratio of polyethyleneimine, phosphate buffer, caffeic acid and 1-(3-dimethylaminopropyl)-3-ethylcarbodiimide is 1:(15-20):(0.5-0.7):(0.9-1.0), and the concentration of nitric acid is 1M.
[0016] Furthermore, in step (1), the concentration of the mixed solution is 10 mg / mL, and its mass is 100-120 times the mass of polyethyleneimine.
[0017] Furthermore, in step (2), the mass ratio of salicylaldehyde, anhydrous ethanol and ethylenediamine is 1:(8-10):(0.25-0.30).
[0018] Furthermore, in the step (2), the mass ratio of the hydroxyl-containing monomer, castor oil triglycidyl ether and tetrabutylammonium bromide is 1:(8-10):(0.1-0.3).
[0019] Furthermore, in the step (3), the mass ratio of the modified graphene oxide, deionized water and the hyperbranched epoxy compound is 1:(200-300):(0.4-0.6).
[0020] Furthermore, in the step (3), the mass ratio of the hyperbranched epoxy compound, octadecanethiol, perfluorodecanethiol and 2-hydroxy-2-methylpropiophenone is 1:(0.5-1.0):(1-2):(0.1-0.3).
[0021] Furthermore, in step (3), the process conditions of ultraviolet irradiation are: irradiation wavelength 360-400nm, irradiation time 0.5-1.0h, irradiation intensity 20-35mW / cm 2 .
[0022] Furthermore, the epoxy diluent is 1,6-hexanediol diglycidyl ether.
[0023] Furthermore, the curing agent is isophorone diamine curing agent.
[0024] Furthermore, the thickness of the corrosion-resistant coating is 50-100 μm.
[0025] Furthermore, the curing process conditions are curing at 120-150° C. for 4-8 hours.
[0026] Compared with the prior art, the present invention has the following beneficial effects: 1. A high-strength alloy material based on rail transit vehicles and a processing technology thereof of the present invention, through the reaction of the amino group in polyethyleneimine with the carboxyl group in caffeic acid, introduces catechol groups and double bonds with adhesion properties, which can not only chelate with metal ions, but also increase the cross-linking density inside the coating to form a rough surface morphology, and this roughness helps to enhance the adhesion between the coating and the substrate, thereby preparing a polymer anti-corrosion coating with sustained and long-lasting adhesion properties, and significantly improving the anti-corrosion effect; polyethyleneimine containing a large amount of amino groups is then used as a bridge to react with the epoxy group in graphene oxide, and the amino groups are introduced onto the surface of graphene oxide to obtain modified graphene oxide; Based on the condensation reaction of salicylaldehyde and ethylenediamine, a two-functional A 2 The monomer, i.e., the hydroxyl-containing monomer, introduces heteroatoms (N atoms) to provide a basis for subsequent fast curing and anti-corrosion performance, and then the hydroxyl-containing monomer and castor oil triglycidyl ether undergo a ring-opening reaction through proton transfer polymerization, thereby generating a macromolecular structure with less intermolecular chain entanglement and low viscosity, thereby obtaining a hyperbranched epoxy compound with a double bond; then, the amino group on the modified graphene oxide reacts with the hyperbranched epoxy compound to improve the compatibility of the modified graphene oxide with the epoxy resin matrix; finally, octadecyl mercaptan and perfluorodecyl mercaptan are added, and hydrophobic long-chain alkyl and fluorine-containing groups are introduced through a thiol-ene click reaction, which significantly improves the hydrophobicity of the material, helps to reduce the penetration of water, and improves the anti-corrosion performance, especially the application effect in a humid environment.
[0027] 2. In the high-strength alloy material and its processing technology based on rail transit vehicles of the present invention, the addition of Zn element can increase the fluidity of alloy liquid, better realize the formability of materials, and reduce the occurrence of defects; Y can enhance the high temperature resistance and oxidation resistance of magnesium alloy, and improve the stability of alloy in high temperature environment. At the same time, Y can also improve the corrosion resistance of alloy and prolong the service life; Gd can be used as a strengthening element in alloy to promote the precipitation of second phase, improve the strength and toughness of alloy, especially perform well under high temperature conditions, thereby further enhancing the mechanical properties of materials; Zr element can effectively refine grains and improve the tensile strength and toughness of materials; Adding Ca element can significantly improve the flame retardant properties of magnesium alloy, so that the material remains relatively intact under high temperature oxidation conditions, which is conducive to improving safety; The addition of Sn element can significantly refine the cast alloy grains, promote the precipitation of second phase, help to improve the strength and fatigue resistance of materials, and improve the overall mechanical properties; By reasonably adding these elements, the high-strength alloy material prepared by the present invention has achieved excellent performance in mechanical properties, flame retardant properties, corrosion resistance, etc., meeting the application requirements of rail transit vehicles. DETAILED DESCRIPTION
[0028] The technical solutions in the embodiments of the present invention are described clearly and completely below. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of them. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.
[0029] In this embodiment, Mg is pure magnesium ingot, brand Mg99.98; Zn is pure zinc ingot, brand Zn99.995; Y is Mg-Y master alloy, brand MgY30; Gd is Mg-Gd master alloy, brand MgGd30; Zr is Mg-Zr master alloy, brand MgZr25; Ca is Mg-Ca master alloy, brand MgCa30; Sn is Mg-Sn master alloy, brand MgSn20; Epoxy resin: brand E51; Polyethyleneimine: CAS number is 9002-98-6; Graphene oxide: thickness 1-3nm, diameter 4-7μm, number of layers 2-5; Mica powder: particle size is 1250 mesh; Defoamer: BYK-057; Leveling agent: BYK-333.
[0030] In the following examples and comparative examples, 1 part is equal to 10 g.
[0031] Embodiment 1: A processing technology for high-strength alloy materials for rail transit vehicles, comprising the following processes: Step S1: smelting the raw material at 740°C, cooling it to 720°C after melting, keeping it at this temperature for 10 minutes, and casting it to obtain an ingot; Step S2: subjecting the ingot to solution treatment (keeping at 515°C for 8 hours, water quenching) and aging treatment (keeping at 220°C for 10 hours, air cooling) in sequence to obtain an alloy material; Step S3: 5 parts of the composite, 10 parts of mica powder, 8 parts of the curing agent and 10 parts of the epoxy diluent are mixed evenly, 50 parts of epoxy resin, 0.2 parts of the defoaming agent and 0.1 parts of the leveling agent are added, and ultrasonic treatment is performed to obtain a corrosion-resistant coating; the surface of the alloy material is grinded, polished, cleaned and dried in sequence, and then the corrosion-resistant coating is coated, and after curing (curing at 120° C. for 8 hours), a corrosion-resistant coating is formed to obtain a high-strength alloy material; the raw materials include the following chemical compositions in mass percentage: Zn: 1%, Y: 3.6%, Gd: 1.2%, Zr: 0.4%, Ca: 0.05%, Sn: 0.3%, and the balance is Mg; The preparation method of the complex is as follows: Step (1): 5 parts of polyethyleneimine and 75 parts of phosphate buffer are mixed evenly, 1M nitric acid is used to adjust the pH of the system to 5.0, 2.5 parts of caffeic acid and 4.5 parts of 1-(3-dimethylaminopropyl)-3-ethylcarbodiimide are added, and the reaction is carried out for 2 hours to obtain a modified polyethyleneimine solution, 500 parts of a mixed solution of 10 mg / mL graphene oxide and DMF are added dropwise for 1 hour, and the mixture is reacted for 6 hours. The mixture is cooled to room temperature, filtered, washed, and dried to obtain modified graphene oxide; Step (2): Under nitrogen protection, 1 part of salicylaldehyde and 8 parts of anhydrous ethanol are mixed evenly, 0.25 parts of ethylenediamine are added dropwise over 30 minutes, the mixture is reacted at 70°C for 3 hours, cooled to room temperature, filtered, washed, and dried to obtain a hydroxyl-containing monomer; Under nitrogen protection, 0.25 parts of hydroxyl-containing monomer, 2 parts of castor oil triglycidyl ether, and 0.025 parts of tetrabutylammonium bromide are mixed evenly, the mixture is reacted at 70°C for 4 hours, cooled to room temperature, filtered, washed, and dried to obtain a hyperbranched epoxy compound; Step (3): ultrasonically disperse 5 parts of modified graphene oxide in 1000 parts of deionized water, adjust the pH to 9 with sodium hydroxide, add 2 parts of hyperbranched epoxy compound and mix evenly, react for 6 hours, then add 1 part of octadecyl mercaptan, 2 parts of perfluorodecyl mercaptan and 0.2 parts of 2-hydroxy-2-methylpropiophenone and mix evenly, and irradiate with ultraviolet light (irradiation wavelength 360nm, irradiation time 0.5h, irradiation intensity 20mW / cm 2 ), washing, filtering and drying to obtain a composite.
[0032] Embodiment 2: A processing technology for high-strength alloy materials for rail transit vehicles, comprising the following processes: Step S1: smelting the raw material at 750°C, cooling it to 725°C after melting, keeping it at this temperature for 15 minutes, and casting it to obtain an ingot; Step S2: subjecting the ingot to solution treatment (keeping at 520°C for 10 hours, water quenching) and aging treatment (keeping at 240°C for 12 hours, air cooling) in sequence to obtain an alloy material; Step S3: 10 parts of the composite, 15 parts of mica powder, 10 parts of the curing agent and 15 parts of the epoxy diluent are mixed evenly, 55 parts of epoxy resin, 0.25 parts of the defoaming agent and 0.15 parts of the leveling agent are added, and ultrasonic treatment is performed to obtain a corrosion-resistant coating; the surface of the alloy material is grinded, polished, cleaned and dried in sequence, and then the corrosion-resistant coating is coated, and after curing (curing at 140° C. for 6 hours), a corrosion-resistant coating is formed to obtain a high-strength alloy material; the raw materials include the following chemical compositions in mass percentage: Zn: 1.5%, Y: 4%, Gd: 1.3%, Zr: 0.5%, Ca: 0.08%, Sn: 0.4%, and the balance is Mg; The preparation method of the complex is as follows: Step (1): 10 parts of polyethyleneimine and 180 parts of phosphate buffer are mixed evenly, and the pH value of the system is adjusted to 5.3 using nitric acid, 6 parts of caffeic acid and 9.5 parts of 1-(3-dimethylaminopropyl)-3-ethylcarbodiimide are added, and the reaction is carried out for 2.5 hours to obtain a modified polyethyleneimine solution, and 1100 parts of a mixed solution of 10 mg / mL graphene oxide and DMF are added dropwise for 1.5 hours, and the mixture is reacted for 7 hours. The mixture is cooled to room temperature, filtered, washed, and dried to obtain modified graphene oxide; Step (2): Under nitrogen protection, 1 part of salicylaldehyde and 9 parts of anhydrous ethanol are mixed evenly, 0.28 parts of ethylenediamine are added dropwise over 40 minutes, the mixture is reacted at 75°C for 4 hours, cooled to room temperature, filtered, washed, and dried to obtain a hydroxyl-containing monomer; Under nitrogen protection, 0.6 parts of hydroxyl-containing monomer, 5.4 parts of castor oil triglycidyl ether, and 0.12 parts of tetrabutylammonium bromide are mixed evenly, the mixture is reacted at 75°C for 5 hours, cooled to room temperature, filtered, washed, and dried to obtain a hyperbranched epoxy compound; Step (3): 10 parts of modified graphene oxide were ultrasonically dispersed in 2500 parts of deionized water, and the pH was adjusted to 9.5 with sodium hydroxide. 5 parts of hyperbranched epoxy compound were added and mixed evenly. The mixture was reacted for 7 hours. Then 4 parts of octadecyl mercaptan and 7.5 parts of 2-hydroxy-2-methylpropiophenone were added and mixed evenly. The mixture was irradiated with ultraviolet light (irradiation wavelength 380 nm, irradiation time 0.8 h, irradiation intensity 25 mW / cm 2 ), washing, filtering and drying to obtain a composite.
[0033] Embodiment 3: A processing technology for high-strength alloy materials for rail transit vehicles, comprising the following processes: Step S1: smelting the raw material at 760° C., cooling it to 730° C. after melting, keeping it warm for 20 minutes, and casting it to obtain an ingot; Step S2: subjecting the ingot to solution treatment (keeping at 535°C for 12 hours, water quenching) and aging treatment (keeping at 260°C for 14 hours, air cooling) in sequence to obtain an alloy material; Step S3: 15 parts of the composite, 20 parts of mica powder, 12 parts of the curing agent and 20 parts of the epoxy diluent are mixed evenly, 60 parts of epoxy resin, 0.3 parts of the defoaming agent and 0.2 parts of the leveling agent are added, and ultrasonic treatment is performed to obtain a corrosion-resistant coating; the surface of the alloy material is grinded, polished, cleaned and dried in sequence, and then the corrosion-resistant coating is coated, and after curing (curing at 150° C. for 4 hours), a corrosion-resistant coating is formed to obtain a high-strength alloy material; the raw materials include the following chemical compositions in mass percentage: Zn: 2%, Y: 4.2%, Gd: 1.4%, Zr: 0.6%, Ca: 0.10%, Sn: 0.5%, and the balance is Mg; The preparation method of the complex is as follows: Step (1): 15 parts of polyethyleneimine and 300 parts of phosphate buffer are mixed evenly, nitric acid is used to adjust the pH of the system to 5.5, 10.5 parts of caffeic acid and 15 parts of 1-(3-dimethylaminopropyl)-3-ethylcarbodiimide are added, and the reaction is carried out for 3 hours to obtain a modified polyethyleneimine solution, 1800 parts of a mixed solution of 10 mg / mL graphene oxide and DMF are added dropwise for 2 hours, and the mixture is reacted for 8 hours. The mixture is cooled to room temperature, filtered, washed, and dried to obtain modified graphene oxide; Step (2): Under nitrogen protection, 1 part of salicylaldehyde and 10 parts of anhydrous ethanol are mixed evenly, 0.3 parts of ethylenediamine are added dropwise over 50 minutes, the mixture is reacted at 80°C for 5 hours, cooled to room temperature, filtered, washed, and dried to obtain a hydroxyl-containing monomer; Under nitrogen protection, 1 part of a hydroxyl-containing monomer, 10 parts of castor oil triglycidyl ether, and 0.3 parts of tetrabutylammonium bromide are mixed evenly, the mixture is reacted at 80°C for 6 hours, cooled to room temperature, filtered, washed, and dried to obtain a hyperbranched epoxy compound; Step (3): 15 parts of modified graphene oxide were ultrasonically dispersed in 4500 parts of deionized water, and the pH was adjusted to 10 with sodium hydroxide, and 9 parts of hyperbranched epoxy compound were added and mixed evenly, and the mixture was reacted for 8 hours, and then 9 parts of octadecyl mercaptan and 18 parts of 2-hydroxy-2-methylpropiophenone were added and mixed evenly, and then irradiated with ultraviolet light (irradiation wavelength 400nm, irradiation time 1.0h, irradiation intensity 35mW / cm 2 ), washing, filtering and drying to obtain a composite.
[0034] Comparative Example 1: The raw materials include the following chemical components in mass percentage: Zn: 0.5%, Y: 2%, Gd: 0.5%, Zr: 0.2%, Ca: 0.01%, Sn: 0.2%, and the balance is Mg. The other steps and processes are the same as those in Example 1.
[0035] Comparative Example 2: A processing technology for high-strength alloy materials based on rail transit vehicles, comprising the following processes: Compared with Example 2, in Comparative Example 2, the composite is replaced with graphene oxide of the same mass, and the other steps are the same as those of Example 2.
[0036] Comparative Example 3: A processing technology for high-strength alloy materials based on rail transit vehicles, comprising the following processes: Compared with Example 2, Comparative Example 3 does not include step (2), and no hyperbranched epoxy compound is added in step (3). The other steps are the same as those of Example 2.
[0037] Comparative Example 4: A processing technology for high-strength alloy materials based on rail transit vehicles, comprising the following processes: The preparation method of the complex is as follows: Step (1): 10 parts of polyethyleneimine and 180 parts of phosphate buffer are mixed evenly, and the pH value of the system is adjusted to 5.3 using nitric acid, 6 parts of caffeic acid and 9.5 parts of 1-(3-dimethylaminopropyl)-3-ethylcarbodiimide are added, and the reaction is carried out for 2.5 hours to obtain a modified polyethyleneimine solution, and 1100 parts of a mixed solution of 10 mg / mL graphene oxide and DMF are added dropwise for 1.5 hours, and the mixture is reacted for 7 hours. The mixture is cooled to room temperature, filtered, washed, and dried to obtain modified graphene oxide; Step (2): Under nitrogen protection, 1 part of salicylaldehyde and 9 parts of anhydrous ethanol are mixed evenly, 0.28 parts of ethylenediamine are added dropwise over 40 minutes, the mixture is reacted at 75°C for 4 hours, cooled to room temperature, filtered, washed, and dried to obtain a hydroxyl-containing monomer; Under nitrogen protection, 0.6 parts of hydroxyl-containing monomer, 5.4 parts of castor oil triglycidyl ether, and 0.12 parts of tetrabutylammonium bromide are mixed evenly, the mixture is reacted at 75°C for 5 hours, cooled to room temperature, filtered, washed, and dried to obtain a hyperbranched epoxy compound; Step (3): ultrasonically disperse 10 parts of modified graphene oxide in 2500 parts of deionized water, adjust the pH to 9.5 with sodium hydroxide, add 1 part of hyperbranched epoxy compound and mix evenly, react for 7 hours, then add 4 parts of octadecyl mercaptan and 7.5 parts of 2-hydroxy-2-methylpropiophenone and mix evenly, irradiate with ultraviolet light (irradiation wavelength 380 nm, irradiation time 0.8 h, irradiation intensity 25 mW / cm2), wash, filter and dry to obtain a composite; Compared with Example 2, in step (3) of Comparative Example 4, the mass ratio of modified graphene oxide to hyperbranched epoxy compound is 1:0.1, and the other steps are the same as those of Example 2.
[0038] Experiment: Take the high-strength alloy materials obtained in Examples 1-3 and Comparative Examples 1-4, prepare samples, test their properties respectively and record the test results: The tensile strength was determined according to GB / T228.1-2010 "Tensile tests on metallic materials - Part 1: Test methods at room temperature". The sample size was a bar with a diameter of 16 mm. The room temperature tensile test was performed on a CMT-5105 universal testing machine. The corrosion resistance was determined according to GB / T 1771-2007 “Determination of resistance of paints and varnishes to neutral salt spray”. The experimental steps were as follows: the sample size was φ10mm×2mm, two cross cracks were drawn on the coating surface, and then the sample was placed in a salt spray test chamber. At the test temperature of (35±2)℃ and pH value of about 6.7-7.5, a 5% NaCl solution was used as the spray medium. After 720h of the salt spray test, the performance of the sample was evaluated.
[0039] The contact angle was measured using a JC2000DM contact angle meter, and the volume of deionized water was 2 μL.
[0040] The test results are as follows:
[0041] According to the data in the above table, we can clearly draw the following conclusions: 1. Compared with Examples 1-3, the tensile strength of the product obtained in Comparative Example 1 decreases, indicating that the performance of the alloy material prepared by the present invention is affected by its component ratio. When the component ratio is selected within the range, the prepared product has better performance.
[0042] 2. Compared with Examples 1-3, the hydrophobicity and corrosion resistance of the products obtained in Comparative Examples 2 and 3 are both reduced, indicating that compared with graphene oxide, the composite phase prepared by the present invention is more superior in hydrophobic effect and corrosion resistance, thereby effectively improving the corrosion resistance of the magnesium alloy; at the same time, the addition of hyperbranched epoxy compounds in the present invention can further improve the corrosion resistance, and can provide more reaction sites, which is beneficial to the grafting of hydrophobic long-chain monomers and fluorine-containing monomers, thereby further improving the hydrophobic effect.
[0043] 3. Compared with Examples 1-3, the hydrophobicity and corrosion resistance of the product obtained in Comparative Example 4 are both reduced. It can be seen that when the addition amount of the hyperbranched epoxy compound is reduced, the corrosion resistance and hydrophobicity of the material will be reduced.
[0044] It will be apparent to those skilled in the art that the present invention is not limited to the details of the exemplary embodiments described above and that the present invention can be implemented in other specific forms without departing from the spirit or essential features of the present invention. Therefore, the embodiments should be considered exemplary and non-restrictive in all respects, and the scope of the present invention is defined by the appended claims rather than the above description, and it is intended that all changes falling within the meaning and scope of the equivalent elements of the claims be included in the present invention.
Claims
1. A processing technology for high-strength alloy materials for rail transit vehicles, characterized in that: The steps include: Step S1: smelting the raw materials at 740-760° C., cooling the temperature to 720-730° C. after melting, keeping the temperature for 10-20 minutes, and casting to obtain an ingot; Step S2: subjecting the ingot to solution treatment and aging treatment in sequence to obtain an alloy material; Step S3: uniformly mixing the composite, mica powder, curing agent and epoxy diluent, adding epoxy resin, defoaming agent and leveling agent, and performing ultrasonic treatment to obtain a corrosion-resistant coating; grinding, polishing, cleaning and drying the surface of the alloy material in sequence, coating the corrosion-resistant coating, and forming a corrosion-resistant coating after curing to obtain a high-strength alloy material; The raw material includes the following chemical components by mass percentage: Zn: 1-2%, Y: 3.6-4.2%, Gd: 1.2-1.4%, Zr: 0.4-0.6%, Ca: 0.05-0.10%, Sn: 0.3-0.5%, and the balance is Mg; The preparation method of the composite is as follows: Step (1): uniformly mix polyethyleneimine and phosphate buffer, use nitric acid to adjust the pH of the system to 5.0-5.5, add caffeic acid and 1-(3-dimethylaminopropyl)-3-ethylcarbodiimide, react for 2-3 hours to obtain a modified polyethyleneimine solution, add a mixed solution of graphene oxide and DMF dropwise for 1-2 hours, react for 6-8 hours, cool to room temperature, filter, wash and dry to obtain modified graphene oxide; Step (2): under nitrogen protection, salicylaldehyde and anhydrous ethanol are mixed evenly, ethylenediamine is added dropwise for 30-50 minutes, the mixture is reacted at 70-80°C for 3-5 hours, the mixture is cooled to room temperature, filtered, washed and dried to obtain a hydroxyl-containing monomer; the hydroxyl-containing monomer, castor oil triglycidyl ether and tetrabutylammonium bromide are mixed evenly, the mixture is reacted at 70-80°C for 4-6 hours, the mixture is cooled to room temperature, filtered, washed and dried to obtain a hyperbranched epoxy compound; Step (3): ultrasonically disperse the modified graphene oxide in deionized water, adjust the pH to 9-10 with sodium hydroxide, add the hyperbranched epoxy compound and mix evenly, react for 6-8 hours, then add octadecyl mercaptan, perfluorodecyl mercaptan and 2-hydroxy-2-methylpropiophenone and mix evenly, irradiate with ultraviolet light, wash, filter and dry to obtain a composite.
2. The processing technology of high-strength alloy material for rail transit vehicles according to claim 1 is characterized in that: The solution treatment process is to keep the temperature at 515-535° C. for 8-12 hours and then quench in water.
3. The processing technology of high-strength alloy material for rail transit vehicles according to claim 1 is characterized in that: The aging treatment process is to keep the temperature at 220-260° C. for 10-14 hours and air cool.
4. The processing technology of high-strength alloy material for rail transit vehicles according to claim 1 is characterized in that: The corrosion-resistant coating comprises the following components by weight: 50-60 parts of epoxy resin, 5-15 parts of compound, 10-20 parts of mica powder, 10-20 parts of epoxy diluent, 8-12 parts of curing agent, 0.2-0.3 parts of defoaming agent and 0.1-0.2 parts of leveling agent.
5. The processing technology of high-strength alloy material based on rail transit vehicles according to claim 5 is characterized in that: The epoxy resin is E51 epoxy resin.
6. The processing technology of high-strength alloy material for rail transit vehicles according to claim 5 is characterized in that: The epoxy diluent is 1,6-hexanediol diglycidyl ether.
7. The processing technology of high-strength alloy material for rail transit vehicles according to claim 1 is characterized in that: In step (2), the mass ratio of the hydroxyl-containing monomer, castor oil triglycidyl ether and tetrabutylammonium bromide is 1:(8-10):(0.1-0.3).
8. The processing technology of high-strength alloy material for rail transit vehicles according to claim 1 is characterized in that: In step (3), the mass ratio of modified graphene oxide, deionized water and hyperbranched epoxy compound is 1:(200-300):(0.4-0.6).
9. A high-strength alloy material for rail transit vehicles obtained by the processing technology according to any one of claims 1 to 8.
Citation Information
Patent Citations
Corrosion-resistant bolt and anticorrosive treatment method thereof
CN109628852A
Modified graphene oxide anticorrosive coating and preparation method thereof
CN113292902A
Preparation process of high-strength corrosion-resistant metal profile for rail transit
CN113981260A
Automobile top cover aluminum alloy shell and processing process thereof
CN114029214A
Preparation process of aluminum alloy for new energy vehicle body
CN117265349A
Cited By
High-strength alloy steel plate and processing technology thereof
CN120210647A
High-strength cast aluminum alloy material for 5G case and preparation method of high-strength cast aluminum alloy material
CN120989431A
A high-strength cast aluminum alloy material for a 5G case and a preparation method thereof
CN120989431B